COFFEE AGROFORESTRY DESIGN BASED ON HYDROLOGY IN PALINTANG, CILENGKRANG, WEST JAVA - Qorry Aina, Savira
Since the 19th century, the coffee plant is an important commodity in international trade. Coffee consumption per capita in Indonesia is currently 1.11 kg/capita/year and will continue to increase. In the context of developing coffee plants, information related to water management such as hydrological processes (infiltration and available water storage in the soil) is needed. The purpose of this study was to determine the soil infiltration value, groundwater storage value, and the effect of the presence of eucalyptus (Eucalyptus sp.) and pine (Pinus merkusii) as coffee (Coffea arabica) shade plants on infiltration and water storage in coffee agroforestry land in Patrol Palintang, Cipanjalu, Kec. Cilengkrang, Bandung, West Java. The method used in this research is field observation and laboratory analysis. The research was conducted in two different places, namely coffee plantations under eucalyptus shade and coffee plantations under pine shade. From each place data collection was carried out at 5 different points. Parameters observed were infiltration and water storage in the soil as well as the physical and chemical properties of the soil which were carried out in three periods. The results of the study found an average infiltration on coffee plantations shaded by Eucalyptus sp. of 9.62 mm and on coffee plantations shaded by Pinus merkusii of 18.66 mm. The average groundwater storage in coffee fields shaded by Eucalyptus sp. of 296.25 mm and on coffee plantations shaded by Pinus merkusii of 255.16 mm. Soil infiltration was influenced by the type of shade on coffee plantations (p <0.05) and the thickness of the litter. The amount of groundwater storage was not affected by differences in the type of shade on coffee plantations (p > 0.05). Water storage is affected by the water content and the physical characteristics of the soil.